Pentingnya Literasi Digital untuk Meningkatkan Kemampuan Berpikir Kritis dan Kemampuan Pemecahan Masalah Mahasiswa di era digital - Aida Fiqtianisa; Purwanti (CV. ITTC INDONESIA, 2025)
Digital literacy is essential to improve students' critical thinking and problem-solving skills in the modern era. The purpose of this study is to reveal the importance of digital literacy. This study involved students aged 18 to 24 as respondents, using qualitative methods and a grounded research approach. Researchers were able to gain a better understanding of the relationship between digital literacy, critical thinking and problem solving in higher education as data was collected through participatory observation and in-depth interviews. According to this research, students who acquire digital literacy through technology-based learning can acquire better critical thinking and problem-solving skills. The results of this study can be the basis for better educational policies that help students prepare themselves to face challenges in the technological era.